La serpiente en las monedas : transmisión iconográfica de una antigua creencia - Vázquez Hoys, Ana María (Espacio Tiempo y Forma. Serie II, Historia Antigua, 1993)
We present here a brief study about the evolution of the figure of the snake and its significance throughout the times, besides its particular presence in some antigüe coins. While in the greek ones the snake is a beneficent genius, in those of the Román empire it will represent the enemies of political and religious powers. In memory of the recently deceased professor María Gimbutas